USING EFFECTIVE IN-SERVICE TRAINING TO IMPACT E.S.P TEACHERS’ PERFORMANCE IN TECHNICAL SCHOOLS IN BENIN - KOUTCHADE, INNOCENT SOUROU; PATINVOH AGBAYAHOUN, JUVENALE; MINAFLINOU BANKOLE, ESTELLE SÈYIVÈ; ADJAHOUINOU ALOKPO, Mahoussi Euphrasie (My University, 2020)
Despite the numerous teaching/learning approaches witnessed by the educational system in Benin and the current implementation of the Competency- Based Approach, teachers of English in technical schools in Benin are still using the Objective-based approach which makes the teacher being the center of the teaching/learning process although previous studies suggested the Competency Based Approach as the most appropriate one for ESP teaching (Djelil, 2012; Bratanych and Vyshnevska, 2018). Besides, these teachers are not qualified for teaching ESP. This situation compromises learners’ ability to use English as a tool for communication both in their daily lives and in their future professions.The present study aims not only to find out teachers’ perceptions and practices of TESP but also to point out the scarcity of effective and efficient in-service training opportunities for ESP teachers in technical schools in Benin. It also intends to bring up the positive impact of well-organised in-service programs on teachers’ performances. To reach those goals, questionnaires have been addressed to fifty (50) ESP teachers from whom ten (10) have been observed in class situation in nine technical schools. Two (02) English teaching advisers have been interviewed. The findings have revealed that teachers have a positive perception of TESP in theory but fail to match theory with practice. It has also been proven that there is an absence of qualified ESP teachers and inspectors added to a shortage of qualified ESP teaching advisers in Benin technical schools. Furthermore, the lack of appropriate teaching/learning materials and of adequate training in TESP has created a hindrance for students’ performance in ESP classrooms. Thanks to the results of this research, a special attention can be granted to TESP in Benin, both in Teacher Training Colleges and in in-service teacher training programs as teachers’ professional development fights complacency and works for the betterment of learners’ output. Keywords: TESP
Keywords: TESP; TEFL; Teacher professional development; Competency-based; approach; technical schools